2005
DOI: 10.1111/j.1365-2591.2005.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional, non‐destructive visualization of vertical root fractures using flat panel volume detector computer tomography: an ex vivoin vitro case report

Abstract: The FD-VCT is an innovative diagnostic tool for non-destructive, three-dimensional evaluation of extracted teeth in pre-clinical and experimental studies. The FD-VCT allows precise visualization and evaluation of vertical root fractures or cracks in extracted teeth. Clinical application of the system may be possible if technical modifications reduce the exposure dose: the high resolution detector systems of the FD-VCT should be combined with radiation systems that focus the radiation to the area of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 21 publications
(35 reference statements)
1
47
0
8
Order By: Relevance
“…2 However, the higher cost and radiation dose associated with conventional CT outweigh these advantages in the light of endodontic practice. 5,6 Cone-beam CT (CBCT) involves lesser radiation dose and yields higher spatial resolution than conventional CT. Prototype local CT systems, flat-panel detector CBCT systems that are used to scan ex vivo samples, are found to be valuable for detecting root fractures, 7,8 but they cannot be used to scan patients. Clinical dental CBCT systems appear to be superior to conventional dental radiography in detecting artificially created root fractures.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, the higher cost and radiation dose associated with conventional CT outweigh these advantages in the light of endodontic practice. 5,6 Cone-beam CT (CBCT) involves lesser radiation dose and yields higher spatial resolution than conventional CT. Prototype local CT systems, flat-panel detector CBCT systems that are used to scan ex vivo samples, are found to be valuable for detecting root fractures, 7,8 but they cannot be used to scan patients. Clinical dental CBCT systems appear to be superior to conventional dental radiography in detecting artificially created root fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies 17,[38][39][40] substantiate the good diagnostic capabilities of fpVCT for small bone structures. Obenauer et al 41 demonstrated that with the prototype of a fpVCT the imaging of different phantoms can be distinctively improved in comparison to the results afforded by MSCT.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] It has already been reported 16,19 that fpVCT is superior to the MSCT with regard to visualization of the sutural structures.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] It also allows classification in terms of direction (horizontal, vertical, or oblique) and fracture location (apical, middle, or cervical third of the root). 12 Nevertheless, it can be seen that in the majority of cases of fracture, the tooth has received endodontic treatment and the insertion of intraradicular posts. These radiopaque and/or metallic filling materials in the CBCT viewing field may generate artifacts in the form of striations or streaks, known as the beam-hardening effect, which could compromise root fracture detection in terms of the sensitivity and specificity of the diagnosis.…”
Section: Introductionmentioning
confidence: 99%